Proceedings of 1998 International Symposium on Electrical Insulating Materials. 1998 Asian International Conference on Dielectr
DOI: 10.1109/iseim.1998.741760
|View full text |Cite
|
Sign up to set email alerts
|

Impact of carbon particles on the impulse flashover behavior of different solid/liquid interfaces in a non-uniform field

Abstract: This paper reports on experimental investigations dealing with the influence of carbon particles on the lightning impulse flashover behavior of the interface between insulating rods of different permittivities and surface structures and transformer oil in a non-uniform electrical field. The results reveal that for negative lightning impulse stress carbon particles in the oil act as defects due to their positive polarity and thus reduce the breakdown and flashover strength of all investigated materials distinct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 7 publications
2
5
0
Order By: Relevance
“…In terms of the breakdown mechanism, the image charge theory described in [1] appears to be corroborated by the results, insofar as the gaps with solids of higher permittivity are broken down at lower voltages than those with solids of permittivity closer to that of the oil -this result was also found by the authors of [6] under non-uniform field geometry. Similar concepts are explored for ac voltages in [7], where the authors propose two different breakdown mechanisms for an oil-pressboard interface: the first is the electric double layer at the liquid-solid interface, where space charge can drift due to the applied electric field and cause tracking; and the second is the oil boundary layer, associated with high-energy flashover.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…In terms of the breakdown mechanism, the image charge theory described in [1] appears to be corroborated by the results, insofar as the gaps with solids of higher permittivity are broken down at lower voltages than those with solids of permittivity closer to that of the oil -this result was also found by the authors of [6] under non-uniform field geometry. Similar concepts are explored for ac voltages in [7], where the authors propose two different breakdown mechanisms for an oil-pressboard interface: the first is the electric double layer at the liquid-solid interface, where space charge can drift due to the applied electric field and cause tracking; and the second is the oil boundary layer, associated with high-energy flashover.…”
Section: Discussionsupporting
confidence: 66%
“…For three of these media -air, vacuum and compressed gases such as SF 6 -dielectric performance under different conditions of applied voltage are fairly well documented, and reliable test procedures and design criteria have been established. On the other hand, less information is available on the behavior of solid dielectrics immersed in dielectric liquids; an area of high-voltage engineering that has become increasingly important in recent years with the development of new industrial-scale pulsed-power machines to be operated under multi-megavolt regimes.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, the peak applied field necessary to initiate surface breakdown events was found to decrease with increasing relative permittivity of the solid and corresponding increasing permittivity mismatch between the solid and the surrounding mineral oil. This finding is in agreement with those of Taylor [3] and Krins et al [4], both of which studies found that higher flashover voltages were yielded by matching the permittivity of the parallel solid surface to that of the oil in which it was immersed. In the case of self-restoring insulation, for example, mineral oil without a solid spacer, lightning-impulse withstand voltage test methods presently used in the power industry include the multiple-level method and the up-and-down method [2].…”
Section: Introductionsupporting
confidence: 92%
“…However, the needle produces a directional and intense electrical field, which can lead to a rapid electrical failure through the bulk medium when using pressboard as the dielectric. Another approach is to use a parallel plane-plane method with pressboard placed perpendicularly between 2 electrodes and with a small point source created on the surface of one of the plane electrodes and adjacent to the pressboard [13]. This method overlooks the fact that the electric field associated with the electrode arrangement is not separated from the enhanced electrical field arising from the discharge source.…”
Section: The Measurement and Production Of Surface Trackingmentioning
confidence: 99%